“Seeing” with reverence: Dirk Smit on the ethos of interpretation - Mouton, EM (Nederduitse Gereformeerde Teologiese Tydskrif, 2007)
The essay briefly discusses aspects of the contribution of Dirk J Smit, South African systematic theologian and ethicist, to an ethos of responsible (biblical) hermeneutics, an ethos of interpretation that invites and encourages human responses of faith and hope. The crucial starting point of such an ethos, the author argues, is the gift of “seeing” differently, of discerning faithfully, of imagining God’s radical presence in the world.The art of “seeing” with respect to Smit’s thinking is discussed under five interrelated rubrics: (a) Seeing the Bible as foundational resource for Christian theology; (b) Seeing the history of biblical interpretation ethically; (c) Seeing Christian ethos and ethics differently; (d) Seeing people through narratives of God’s grace; and (e) Seeing a transformed society through the calling of the church.With continual reference to the “moral world” of the Judeo-Christian narrative, Smit emphasises memory and hope as powerful mechanisms toward developing the moral home of faith communities. Through liturgy – where the narratives and vision of God’s dynamic yet paradoxical presence are celebrated and nurtured—God’s Spirit continues to invite “communities of character” to reimagine their identity and ethos beyond all stereotypical views of God, humanity and the rest of creation.